STUDENTS REALIZATION OF CONNECTED SPEECH ASPECTS - Patang Hafira; Misnawati Misnawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2014)
This research focuses on three aspects of connected speech. They are assimilation, linking and elision. The objective of the research are to find out the students realization of connected speech aspects which covers assimilation, linking and elision, and to know the students knowledge about those three connected speech aspects. The instruments of the research are reading text and questionnaire. The result of the research shows that in assimilation there are 23 tokens pronouncing correctly and there are 334 tokens which are mispronounced. In linking, 103 tokens are pronounced correctly and 254 tokens are mispronounced. In the last aspect of connected speech, that is elision, it is found that there are 244 tokens which are pronounced correctly by the students, while there are 113 which are mispronounced by the students. It shows that the most mispronounced aspect of connected speech is assimilation. Based on the questionnaire, it is found that the students have good knowledge related to aspect of connected speech. It means that the students still need practicing in order to make them accustomed to pronounce the aspects of connected speech.